2017
DOI: 10.1093/icvts/ivw432
|View full text |Cite
|
Sign up to set email alerts
|

Dual source computed tomography based analysis of stent performance, its association with valvular calcification and residual aortic regurgitation after implantation of a balloon-expandable transcatheter heart valve

Abstract: The SAPIEN ® /SAPIEN XT ® prostheses achieved good degrees of stent expansion and circularity regardless of the morphology of the landing zone. Increased stent ovality was associated with an elevated risk for aortic regurgitation. The total calcification volume, degree of annular ovality and stent expansion were not associated with residual AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…One study has found that the SAPIEN has a mean expansion index of 104.1%, compared to 94% (outflow) found in our study [14] . Another study, however, has shown an expansion index of only 84%, substantially inferior to our findings [15] .This variability may be due to different sizing protocols, and also due to differences in the prevalence of bicuspid valve between studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One study has found that the SAPIEN has a mean expansion index of 104.1%, compared to 94% (outflow) found in our study [14] . Another study, however, has shown an expansion index of only 84%, substantially inferior to our findings [15] .This variability may be due to different sizing protocols, and also due to differences in the prevalence of bicuspid valve between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The same finding has been published by other authors [14] . The eccentricity of the device may be correlated to the degree of PVL [15,17] . New mechanisms of leak prevention, such as polytetrafluoroethylene (PTFE) skirts and embolization coils, may, alongside objectively reducing PVL by occupying small empty spaces of malapposition, avoid that structural deformities stemming from imperfect circularity cause such leaks.…”
Section: Imaging Analysismentioning
confidence: 99%